2021
DOI: 10.3390/jof7060410
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Status of Cryptococcus neoformans and Cryptococcus gattii in Colombia

Abstract: The genus Cryptococcus comprises more than 80 species, including C. neoformans and C. gattii, which are pathogenic to humans, mainly affecting the central nervous system. The two species differ in geographic distribution and environmental niche. C. neoformans has a worldwide distribution and is often isolated from bird droppings. On the contrary, C. gattii is reported in tropical and subtropical regions and is associated with Eucalyptus species. This review aims to describe the distribution of environmental is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 94 publications
1
8
0
Order By: Relevance
“…The phylogenetic analysis performed between the 611 genomes included in the study showed that the vast majority of isolates (97%) corresponded to the VNI molecular type ( Figure 1 and Figure 2 A), confirming previous studies performed by MLST [ 5 , 14 ] and its global distribution [ 41 , 42 ]. By analyzing the genetic variability of VNI and comparing it with the reported isolates from Africa and Asia, the C. neoformans VNI lineage from Colombia presents a comparable variability with isolates from Africa [ 43 ] (Colombian isolates = 102,559 SNPs ( n = 29) vs. African isolates = 105,391 SNPs ( n = 24)).…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…The phylogenetic analysis performed between the 611 genomes included in the study showed that the vast majority of isolates (97%) corresponded to the VNI molecular type ( Figure 1 and Figure 2 A), confirming previous studies performed by MLST [ 5 , 14 ] and its global distribution [ 41 , 42 ]. By analyzing the genetic variability of VNI and comparing it with the reported isolates from Africa and Asia, the C. neoformans VNI lineage from Colombia presents a comparable variability with isolates from Africa [ 43 ] (Colombian isolates = 102,559 SNPs ( n = 29) vs. African isolates = 105,391 SNPs ( n = 24)).…”
Section: Discussionsupporting
confidence: 85%
“…[ 38 ]. Considering that this species has been the most frequently recovered from clinical isolates [ 5 ] and with a wide distribution in different departments and Colombian environments [ 14 , 15 ], this study focused on analyzing the phylogenomic relationship and genetic structure of C. neoformans from 29 Colombian clinical isolates of cerebrospinal fluid.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…C. gattii is an encapsulated yeast that has traditionally been found in tropical and subtropical regions. Outbreaks have been recorded in temperate regions such as the Pacific Northwest of the United States, [5,6] but there have been few reported cases of C. gattii in China. [7] C. neoformans is found worldwide.…”
Section: Discussionmentioning
confidence: 99%